2021
DOI: 10.3390/cancers13071502
|View full text |Cite
|
Sign up to set email alerts
|

MAIT Cells: Partners or Enemies in Cancer Immunotherapy?

Abstract: A recent boom in mucosal-associated invariant T (MAIT) cell research has identified relationships between MAIT cell abundance, function, and clinical outcomes in various malignancies. As they express a variety of immune checkpoint receptors and ligands, and possess strong cytotoxic functions, MAIT cells are an attractive new subject in the field of tumor immunology. MAIT cells are a class of innate-like T cells that express a semi-invariant T cell antigen receptor (TCR) that recognizes microbially derived non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 107 publications
0
32
0
Order By: Relevance
“…Because MAIT cells are also involved in a number of inflammatory and autoimmune disorders as well as malignancies, they are attractive targets for therapeutic approaches (39)(40)(41)(42)(43). The present paper aims to review the evidence indicating that MAIT cells may contribute to the pathogenesis of rheumatic diseases due to the possible role of MAIT cells in SLE, RA, PsA, ankylosing spondylitis (AS), SSc, pSS, systemic vasculitis, polymyalgia rheumatica and dermatomyositis (Table 1).…”
Section: Mait Cells In Rheumatic Diseasesmentioning
confidence: 99%
“…Because MAIT cells are also involved in a number of inflammatory and autoimmune disorders as well as malignancies, they are attractive targets for therapeutic approaches (39)(40)(41)(42)(43). The present paper aims to review the evidence indicating that MAIT cells may contribute to the pathogenesis of rheumatic diseases due to the possible role of MAIT cells in SLE, RA, PsA, ankylosing spondylitis (AS), SSc, pSS, systemic vasculitis, polymyalgia rheumatica and dermatomyositis (Table 1).…”
Section: Mait Cells In Rheumatic Diseasesmentioning
confidence: 99%
“…Nevertheless, UT cell-based cancer immunotherapies have already been considered. To date, UT cell-based clinical trials have shown limited success, although such strategies were proven feasible and safe [ 23 , 199 , 200 , 201 ]. The limited positive outcome observed with UT cell-based cancer immunotherapies may be linked to the reduced proportion of UT cells in cancer patients and/or the emergence of exhausted phenotype upon repeated stimulations.…”
Section: Discussionmentioning
confidence: 99%
“…As far their effects, tumour-infiltrating MAIT cells show reduced IFN-γ and TNF-α generation, with augmented IL-17 production, a cytokine able to increase to tumour angiogenesis. 69 As for the effects of these cells on allergic diseases, several findings have demonstrated that MAIT cells may be involved in asthma. A study reported that augmented rates of MAIT cells in children was correlated with a decreased risk of asthma in subse- therefore, they are both a source and a target of VEGF.…”
Section: Innate Lymphoid Cellsmentioning
confidence: 99%